Inter/Weaving Lives and Discourses. Notes and Reflections on Music Biography and Anti-Biography (Revista Argentina de Musicología, 2021)
The place of biographical studies in musicology has been ambiguous from the inception of the discipline at the end of the nineteenth century until today. Moving in between literature and “auxiliary science”, music biography has been sometimes embraced and often neglected as part of the larger intellectual project of musicology. Nevertheless, there is no question that biographies about musicians have occupied plenty of ink and paper from music scholars in the last two or three centuries. In the process, the genre has survived some of the most important transformations that have taken place in musicology. However, at a moment when critical musicology and sound studies effectively move away from the celebration of “great men of history” and the reproduction of Euro-centric teleologies, and at a time when many fields in. the humanities and social sciences have embraced the ant-racist demands of movements like Black Lives Matter and the calls against gender violence of #MeToo, it would seem plausible for the biographical genre to lose its place in the discipline. Taking my recent book about Cuban-American composer Tania León as a case study, this article questions the current relevance and future viability of a genre that ontologically seems to lack the virtues to travel successfully the paths that the most recent epistemological turns propose to musicology.